Actualization of Moderation in Reasoning at Ma’had Aly Salafiyah Syafi’iyah Sukorejo Situbondo and Its Influence on Istinbâth of Islamic Law - Ainol Yaqin; Moch. Cholid Wardi; Achmad Mulyadi (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
This research aims to find and analyze the moderation in reasoning developed at Ma’had Aly Sukorejo and its influence on the inference of Islamic law. The data collection methods are interviews, observation, and document study. The results of this study found that the moderation of reasoning at Ma’had Aly Sukorejo permeated the space of santri’s thinking because they studied and discussed the discipline of ushul fiqh, maqâshid, and other complementary sciences of ijtihad and then applied them in the practice of Islamic law inference (istinbâth). Their moderations of reasoning cover: 1). thinking that every nushûsh al-syarî’ah connects to its own maqâshid, 2). viewing proportionally between the idealistic and realistic points of view, 3). connecting the text with the current context, 4). not fanatical to any certain school(s), and 5). having openness, dialogue, and tolerance for differences. This reasoning results that the Islamic law products being flexible, adaptive, and beneficial as seen in the case of dialogue in the Friday sermon and marriage registration.